Les autorités traditionnelles et l’État moderne en Afrique Subsaharienne au début du XXIe Siècle - Claude-Hélène Perrot (Cadernos de Estudos Africanos)
This article aims to outline the major common features which characterize the relations between traditional authorities and state in West Africa. The article analyses two actual case-studies. The first focuses on the position adopted and the initiatives taken by traditional authorities in South-Western Ivory Coast, in the face of the crises affecting the country. The second analyses the role of royal history in national memory, based on the case of the commemoration of the centenary of the death of king Gbehanzin in Benin, in December 2006. The article also questions the role of historians in this context.